Hand Posturing Is a Nonverbal Indicator of Catastrophic Thinking for Finger, Hand, or Wrist Injury. Issue 4 (April 2018) - Wilkens, Suzanne C.; Lans, Jonathan; Bargon, Claudia A.; Ring, David; Chen, Neal C.
Abstract: Background: Prior research documents that greater psychologic distress (anxiety/depression) and less effective coping strategies (catastrophic thinking, kinesophobia) are associated with greater pain intensity and greater limitations. Recognition and acknowledgment of verbal and nonverbal indicators of psychologic factors might raise opportunities for improved psychologic health. There is evidence that specific patient words and phrases indicate greater catastrophic thinking. This study tested proposed nonverbal indicators (such as flexion of the wrist during attempted finger flexion or extension of uninjured fingers as the stiff and painful finger is flexed) for their association with catastrophic thinking. Questions/purposes: (1) Do patients with specific protective hand postures during physical examination have greater pain interference (limitation of activity in response to nociception), limitations, symptoms of depression, catastrophic thinking (protectiveness, preparation for the worst), and kinesophobia (fear of movement)? (2) Do greater numbers of protective hand postures correlate with worse scores on these measures? Methods: Between October 2014 and September 2016, 156 adult patients with stiff or painful fingers within 2 months after sustaining a finger, hand, or wrist injury were invited to participate in this study. Six patients chose not to participate as a result of time constraints and one patient was excluded as a result of inconsistent scoring of a possible hand posture, leaving 149 patients for analysis. We asked all patients to complete a set of questionnaires and a sociodemographic survey. We used Patient Reported Outcomes Measurement Information System (PROMIS) Depression, Upper Extremity Physical Function, and Pain Interference computer adaptive test (CAT) questionnaires. We used the Abbreviated Pain Catastrophizing Scale (PCS-4) to measure catastrophic thinking in response to nociception. Finally, we used the Tampa Scale of Kinesophobia (TSK) to assess fear of movement. The occurrence of protective hand postures during the physical examination was noted by both the physician and researcher. For uncertainty or disagreement, a video of the physical examination was recorded and a group decision was made. Results: Patients with one or more protective hand postures did not score higher on the PROMIS Pain Interference CAT (hand posture: 59 [56-64]; no posture: 59 [54-63]; difference of medians: 0; p = 0.273), Physical Function CAT (32 ± 8 versus 34 ± 8; mean difference: 2 [confidence interval CI, -0.5 to 5]; p = 0.107), nor the Depression CAT (48 [41-55] versus 48 [42-53]; difference of medians: 0; p = 0.662). However, having at least one hand posture was associated with a higher degree of catastrophic thinking (PCS scores: 13 [6-26] versus 10 [3-16]; difference of medians: 3; p = 0.0104) and a higher level of kinesophobia (TSK: 40 ± 6 versus 38 ± 6; mean difference: -2 [CI, -4 to -1]; p = 0.0420). Greater catastrophic thinking was associated with a greater number of protective hand postures on average (rho: 0.20, p = 0.0138). Conclusions: Protective hand postures and (based on prior research) specific words and phrases are associated with catastrophic thinking and kinesophobia, less effective coping strategies that hinder recovery. Surgeons can learn to recognize these signs and begin to treat catastrophic thinking and kinesophobia starting with compassion, empathy, and patience and be prepared to add formal support (such as cognitive-behavioral therapy) to help facilitate recovery. Level of Evidence: Level III, diagnostic study.